Intercultural dynamics in higher education: Navigating institutional cultural hubs - Hassan, Sinaria (Journal of International Students, 2025)
Globalization has transformed U.S. higher education institutions into culturally diverse environments where international students navigate complex academic and social landscapes. This study examines the impact of institutional policies, communication styles, and social norms on intercultural engagement and academic integration among international students. The findings reveal that while institutional frameworks uphold academic standards, they often unintentionally marginalize non-Western communication and cultural practices. Peer mentorship, language support, and intercultural training are key strategies for fostering inclusion. This study offers evidence-based recommendations for institutional leaders seeking to enhance international student experiences and promote equitable intercultural engagement in higher education.